Analysis of Green Financing Literacy as Sustainable Financing for Micro, Small, and Medium Enterprises (MSMEs) in the Food Processing Industry Sector - Peby Selviona; Erike Anggraeni; Ersi Sisdianto (Jurnal Kolaboratif Sains, 2024)
This study aims to analyze green financing literacy as sustainable financing for micro, small, and medium enterprises (MSMEs) in the food processing industry sector in Bandar Lampung City. The research method used is descriptive qualitative, focusing solely on MSME actors involved in the production of chips located on Pagar Alam Street in Bandar Lampung City. The study was conducted through interviews and research studies. Based on the analysis conducted, the results indicate that the level of green financing literacy among MSME actors is still low, with many not fully understanding the benefits and mechanisms of this financing. Additionally, challenges in accessing financing and implementing environmentally friendly practices have also been identified. This study is expected to provide recommendations for improving MSME literacy and access to green financing, thereby supporting the development of more sustainable businesses that are responsive to environmental challenges. There is a need for socialization about green financing for MSME actors and the loan procedures from financial institutions.